A Study on Fibonacci and Lucas Bihypernomials - Szynal-Liana Anetta; Włoch Iwona (Discussiones Mathematicae - General Algebra and Applications, 2022)
The bihyperbolic numbers are extension of hyperbolic numbers to four dimensions. In this paper we introduce and study the Fibonacci and Lucas bihypernomials, i.e., polynomials, which are a generalization of the bihyperbolic Fibonacci numbers and the bihyperbolic Lucas numbers, respectively.